Frailty assessment predicts toxicity during first cycle chemotherapy for advanced lung cancer regardless of chronologic age. Issue 1 (January 2019) - Ruiz, Jimmy; Miller, Antonius A.; Tooze, Janet A.; Crane, Sandrine; Petty, William J.; Gajra, Ajeet; Klepin, Heidi D.
Abstract: Background: Improved assessment strategies are needed to individualize treatment for adults of all ages receiving palliative chemotherapy for non-small cell lung cancer (NSCLC). Our aim was to evaluate the utility of the Fried Frailty Index (FFI) and a cancer-specific geriatric assessment (GA) to predict chemotherapy toxicity and overall survival (OS). Methods: We conducted a multi-site pilot study of 50 patients with newly diagnosed advanced NSCLC, age ≥ 18 years. All participants received carboplatin AUC 6, paclitaxel 200 mg/m 2 every 3 weeks. FFI and the GA were administered prior to chemotherapy. A GA toxicity risk score was calculated. Grade 3–5 toxicity was assessed during 1st two cycles of chemotherapy. OS was measured from chemotherapy initiation. Logistic regression and Cox proportional hazards models were fit to estimate the association between baseline characteristics and toxicity and OS respectively. Results: Among 50 participants, 48 received chemotherapy and were evaluable. The mean age was 68.5 y (range 42–86), 79% male, 85% KPS ≥80. The median OS was 8 months. Many (27%) met FFI criteria for frailty with ≥3 impairments. Impairments detected by the GA were common. In multivariable analyses both FFI ≥ 3 and GA toxicity risk score > 7 were independently associated with higher odds of toxicity (Odds ratio [OR] 7.0; 95% confidence interval [CI] 1.1–44.6 and OR 4.3; 95% CI 1.0–17.7, respectively) in first cycle chemotherapy. Neither score was associated with OS. Conclusions: Frailty predicts chemotherapy toxicity during first cycle. Frailty assessment may inform toxicity risk regardless of chronologic age.